Therapeutic effects of phlorotannins in the treatment of neurodegenerative disorders - Kwon, Yoon Ji; Kwon, Oh Ig; Hwang, Hye Jeong; Shin, Hyeon-Cheol; Yang, Sungchil (Frontiers in Molecular Neuroscience, 2023)
Phlorotannins are natural polyphenolic compounds produced by brown marine algae and are currently found in nutritional supplements. Although they are known to cross the blood–brain barrier, their neuropharmacological actions remain unclear. Here we review the potential therapeutic benefits of phlorotannins in the treatment of neurodegenerative diseases. In mouse models of Alzheimer’s disease, ethanol intoxication and fear stress, the phlorotannin monomer phloroglucinol and the compounds eckol, dieckol and phlorofucofuroeckol A have been shown to improve cognitive function. In a mouse model of Parkinson’s disease, phloroglucinol treatment led to improved motor performance. Additional neurological benefits associated with phlorotannin intake have been demonstrated in stroke, sleep disorders, and pain response. These effects may stem from the inhibition of disease-inducing plaque synthesis and aggregation, suppression of microglial activation, modulation of pro-inflammatory signaling, reduction of glutamate-induced excitotoxicity, and scavenging of reactive oxygen species. Clinical trials of phlorotannins have not reported significant adverse effects, suggesting these compounds to be promising bioactive agents in the treatment of neurological diseases. We therefore propose a putative biophysical mechanism of phlorotannin action in addition to future directions for phlorotannin research.